2019
DOI: 10.1104/pp.19.00685
|View full text |Cite
|
Sign up to set email alerts
|

WRKY1 Mediates Transcriptional Regulation of Light and Nitrogen Signaling Pathways

Abstract: Plant responses to multiple environmental stimuli must be integrated to enable them to adapt their metabolism and development. Light and nitrogen (N) are two such stimuli whose downstream signaling pathways must be intimately connected to each other to control plant energy status. Here, we describe the functional role of the WRKY1 transcription factor in controlling genome-wide transcriptional reprogramming of Arabidopsis (Arabidopsis thaliana) leaves in response to individual and combined light and N signals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 65 publications
4
17
0
Order By: Relevance
“…Among the TFs found in this study, WRKY TFs, regulating a variety of hormone signaling pathways [58]; bHLH TFs, one of the largest TF families in plants, regulating plant growth and signal transduction [59]; and bZIP TFs, regulating processes including pathway defense, light, and stress signaling [60], were detected in response to low N stress. These TFs were identified as being responsive to N availability in maize [8], Arabidopsis [56], and rice [57]. Moreover, the PodelWRKY18 (Podel.18G019200) was specifically upregulated in N-efficient and N-inefficient genotypes under low N stress, which was consistent with previously published results [56].…”
Section: Differences In Transcriptional Responses To Low N Stress Andsupporting
confidence: 90%
“…Among the TFs found in this study, WRKY TFs, regulating a variety of hormone signaling pathways [58]; bHLH TFs, one of the largest TF families in plants, regulating plant growth and signal transduction [59]; and bZIP TFs, regulating processes including pathway defense, light, and stress signaling [60], were detected in response to low N stress. These TFs were identified as being responsive to N availability in maize [8], Arabidopsis [56], and rice [57]. Moreover, the PodelWRKY18 (Podel.18G019200) was specifically upregulated in N-efficient and N-inefficient genotypes under low N stress, which was consistent with previously published results [56].…”
Section: Differences In Transcriptional Responses To Low N Stress Andsupporting
confidence: 90%
“…In the current study, TF families such as bHLH, NAC, MYB-related, WRKY, and ERF were identified as being responsive to nitrogen availability, of which the WRKY family’s members were specifically upregulated under low-nitrogen conditions (Table 1). Heerah et al [36] found that WRKY1 activates the transcription of GDH1 , NIA1 , NIA2 , NRT2.1 , and AMT1.1 in Arabidopsis . Imamura et al [37] also found that in Cyanidioschyzon merolae MYB1 can enhance nitrogen assimilation in nitrogen deficiency by regulating NRT, NAR, NIR, and GS expression.…”
Section: Discussionmentioning
confidence: 99%
“…Among the TFs found in this study, WRKY TFs, regulating a variety of hormone signaling pathways [ 59 ]; bHLH TFs, one of the largest TF families in plants, regulating plant growth and signal transduction [ 60 ]; and bZIP TFs, regulating processes including pathway defense, light, and stress signaling [ 61 ], were detected in response to low N stress. These TFs were identified as being responsive to N availability in maize [ 8 ], Arabidopsis [ 57 ], and rice [ 58 ]. Moreover, the PodelWRKY18 (Podel.18G019200) was specifically upregulated in N-efficient and N-inefficient genotypes under low N stress, which was consistent with previously published results [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…These TFs were identified as being responsive to N availability in maize [ 8 ], Arabidopsis [ 57 ], and rice [ 58 ]. Moreover, the PodelWRKY18 (Podel.18G019200) was specifically upregulated in N-efficient and N-inefficient genotypes under low N stress, which was consistent with previously published results [ 57 ].…”
Section: Discussionmentioning
confidence: 99%